A Catalyst of Urban Regeneration of Kuala Lumpur: The River of Life Project - Zuraimi, Ainur Syazwina; Mat Radzuan, Indera Syahrul (Research in Management of Technology and Business, 2020)
The River of Life (RoL) is one of Malaysia’s Economic Transformation Programmes, an initiative that combines high-impact projects and programmes to elevate the country to developed nation status. The objective of the study intends to discover the impacts of RoL that implies the planning and river beautification, which has been outline in the literature. The second objective is to determine the challenges and factors that contribute to the success of RoL project. The mixed approach was used in this study involving the interviews, document reviews and questionnaires survey. The study has discovered the impacts of RoL project from the perspectives of local authorities, private sector as well as stakeholders involved in the project. They have played an important role in ensuring all the challenges arise during the development of the project have been resolved accordingly. The outcomes of this study will guide multiple parties in ensuring better urban lifestyle for future Malaysian.